A Critical Analysis of China’s Role in Global Energy Governance as a Strategy for Energy Security and Seeking Hegemony - Diemas Sukma Hawkins; Nirmala Sari; Indah Chaerunnisa; Farahdiba Kuraini (Purnomo Yusgiantoro Center, 2022)
In the turn of the twenty-first, China has grown to become the largest energy consumer in the world, the largest energy producer globally and has risen to prominence as one of the leaders in the development of alternative and renewable energy sources. This has granted China the status as a leader in global energy governance. But while China has actively participated in international energy markets as a massive competition, this has also been juxtaposed with an odd reluctance to ambitiously participate in global energy regimes. However, under President Xi Jinping this has changed, and China has become more and more dominant in the global energy sector; not just in the market but now in its governance. From its inclusion in international energy institutions to its role in energy development in the Belt and Road Initiative, BRICS and New Development Bank; we can now see how China has expanded its dominance in the energy sector. By using qualitative methods, this paper critically analyses China’s strive to become a global hegemony via dominance in the energy development sector, both as a tool for its energy security as well as to hold geopolitical control over developing nations that rely on China for their energy needs.